A Comprehensive Review: The Correlation Between Intensive Aerobix Exercise and Maximum Heart Rate in Athletes - Harvina Mukrim; Muslim Bin Ilyas (Journal Physical Health Recreation (JPHR), 2025)
This article examines the relationship between intensive aerobic exercise and Maximum Heart Rate (MHR) in athletes, focusing on cardiovascular adaptation and its implications for athletes' performance. Through the analysis of current research, this study shows the significant impact of intensive aerobic exercise on heart rate dynamics and cardiovascular efficiency in trained athletes. This study uses a systematic and comprehensive literature review method related to the relationship between intensive aerobic exercise and maximum heart rate in athletes.